Central obesity and survival in subjects with coronary artery disease: a systematic review of the literature and collaborative analysis with individual subject data - Coutinho, Thais; Goel, Kashish; Corrêa de Sá, Daniel; Kragelund, Charlotte; Kanaya, Alka M; Zeller, Marianne; Park, Jong-Seon; Kober, Lars; Torp-Pedersen, Christian; Cottin, Yves; Lorgis, Luc; Lee, Sang-Hee; et al. (Journal of the American College of Cardiology, 2011)
The aim of this study was to examine the association of central (waist circumference [WC] and waist-hip ratio [WHR]) and total obesity (body mass index [BMI]) measures with mortality in coronary artery disease (CAD) patients. The question of which measure of obesity better predicts survival in patients with CAD is controversial. We searched OVID/Medline, EMBASE, CENTRAL, and Web of Science from 1980 to 2008 and asked experts in the field for unpublished data meeting inclusion criteria, in which all subjects had: 1) CAD at baseline; 2) measures of WC or WHR; 3) mortality data; and 4) a minimum follow-up of 6 months. From 2,188 studies found, 6 met inclusion criteria. We obtained individual subject data from 4, adding unpublished data from a cardiac rehabilitation cohort. A variable called "central obesity" was created on the basis of tertiles of WHR or WC. Cox-proportional hazards were adjusted for age, sex, and confounders. The final sample consisted of 15,923 subjects. There were 5,696 deaths after a median follow-up of 2.3 (interquartile range 0.5 to 7.4) years. Central obesity was associated with mortality (hazard ratio [HR]: 1.70, 95% confidence interval [CI]: 1.58 to 1.83), whereas BMI was inversely associated with mortality (HR: 0.64, 95% CI: 0.59 to 0.69). Central obesity was also associated with higher mortality in the subset of subjects with normal BMI (HR: 1.70, 95% CI: 1.52 to 1.89) and BMI ≥30 kg/m(2) (HR: 1.93, 95% CI: 1.61 to 2.32). In subjects with CAD, including those with normal and high BMI, central obesity but not BMI is directly associated with mortality.